An effective lateral earthquake-resisting system for long-span cable-stayed bridges against near-fault earthquakes. (1st October 2019) - Guan, Zhongguo; You, Han; Li, Jianzhong
Highlights: A new lateral ERS for cable-stayed bridges against near-fault earthquakes. The new ERS consists of elastoplastic cables and a parallel FVD. A new anchor design provides stable plastic performance of the elastoplastic cables. Deformation capacity of the new lateral ERS is multiplied. The new ERS provide enormous instant energy dissipation against pulse actions. Short-period pulses induce significant forces on towers. Long-period pulses result in large lateral displacements. Abstract: This paper presents a new lateral isolation system consisting of elastoplastic cables and a parallel fluid viscous damper (FVD) for long-span cable-stayed bridges against near-fault earthquakes. A new anchor design is proposed to prevent premature failure at anchor locations, and an experimental test was conducted to validate the force–displacement relationship of the elastoplastic cable. With the new anchor design, the tested cable showed stable plastic behaviour, and the total deformation capacity was increased by at least 3.3 times the maximum elastic deformation capacity. Based on the Yongning Yellow River Bridge model, a numerical analysis was conducted to investigate the isolation mechanism of the new lateral earthquake-resisting system (ERS). Compared with a hypothetical system with ideal elastic cables and an identical parallel FVD, the new system led to similar girder–tower displacements and base bending moments, and evidently smaller forces at the girder–tower connections and girder acceleration responses, indicating better isolation effects gained with the introduction of elastoplastic cables, which provide significant instant energy dissipation against the pulse action. Furthermore, synthetic near-fault ground motions were generated, and comprehensive parameter analyses were carried out to investigate the isolation effectiveness of the new lateral ERS against near-fault ground motions with various pulse properties. The results show that the girder–tower displacement of the laterally isolated cable-stayed bridge was dominated by the mode with predominant lateral girder vibration and the tower responses by the mode with predominant lateral tower vibration. Near-fault ground motions with short pulse periods tend to induce significant internal forces on the tower columns, whereas near-fault ground motions with long pulse periods result in large displacement demands on the ERS. Moreover, an evident correlation between the dynamic characteristics of structures and the pulse period of near-fault ground motions is illustrated.